PENGARUH SELF REGULATED LEARNING TERHADAP HASIL BELAJAR SISWA DI SMK - Destiasari, Raniska; Warneri, Warneri; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to know the influence of self regulated learning on tenth grade students’ learning achievement on marketing subjects at SMK Negeri 3 Pontianak. The method is descriptive method with the research form of relationship study, population and samples as many as 72 students. The techniques is direct communication techniques, indirect communication techniques (questionnaires) and documentary study techniques. The prerequisite test in this study is the validity test and reliability test. From the results of a simple linear regression calculation with the help of SPSS program version 16.0, there is a positive influence of self regulated learning on tenth grade students’ learning achievement at SMK Negeri 3 Pontianak. This is seen from the T count greater than on T table or 10,049 > 1,994. With a simple linear regression calculation obtained the equation Y = 5.556 + 0.520 x, which means the value of constants (a) of 5.556 can be interpreted if self regulated learning is worth 0 and student learning outcomes are worth 5.556. The coefficient of determination of this research shows the contribution of X variable effect to the Y variable by 59.3%, while the remainder is influenced by other factors not described in this study.  Keywords:Learning Achievement,Marketing Subjects, Self Regulated Learning